Halyomorpha picus (Hemiptera: Heteroptera: Pentatomidae): first confirmed record from Pakistan and two new junior synonyms - Kment, Petr; Salini, S.; Ahmed, Zubair (Zootaxa, 2021)
We provide the first confirmed record of Halyomorpha picus (Fabricius, 1794) (Hemiptera: Heteroptera: Pentatomoidea: Pentatomidae: Pentatominae: Cappaeini) from Pakistan: Islamabad Capital Territory, and provide habitus photographs and electron scanning micrographs of the male genitalia of the voucher specimens. Two species previously described from Pakistan are found to fit within the morphological variability of H. picus and the following two junior subjective synonyms are proposed: Halyomorpha picus (Fabricius, 1794) = Halyomorpha punjabensis Ahmad & Kamaluddin, 1977, syn. nov., = Halyomorpha azhari Ahmad & Zaidi, 1989, syn. nov. The record of Halyomorpha scutellata Distant, 1879, from Pakistan by Sharif et al. (2020) is based on misidentification of a species of Neohalys Ahmad & Perveen, 1982 (Pentatominae: Halyini) and excluded from Pakistan fauna. Based on the analysis of female genitalia figures provided by Gadalla (2004), the record of H. picus from Egypt represents a misidentification of H. halys Stål, 1855, which extends the distribution of that invasive species to North Africa.